Dengeki Daisy. Vol. 3 - Motomi, Kyousuke (Shojo beat manga., 2011)
Teru decides to move out of Kurosaki's apartment, but she wonders if Kurosaki is actually relieved that she's leaving. As she settles in at her new place, trouble comes knocking when an old business acquaintance of her brother's appears.